A feasible way to increase carbon sequestration by adding dolomite and K-feldspar to soil. Issue 1 (31st December 2016) - Xiao, Leilei; Sun, Qibiao; Yuan, Huatao; Li, Xiaoxiao; Chu, Yue; Ruan, Yulong; Lu, Changmei; Lian, Bin
Abstract: In recent years, many researchers have explored various possible ways to slow down the increase in atmospheric CO2 concentration as this process poses a serious threat to mankind's survival. Mineral weathering is one possible way. Silicate weathering, for example, causes net carbon sequestration and carbonate weathering occurs relatively rapidly. In this study, dolomite and K-feldspar were added to soil to investigate if these minerals can increase carbon sequestration and also improve the available potassium content. The carbon content of amaranth, the organic and inorganic carbon content of the soil, two kinds of enzymes (polyphenol oxidase and urease), and the available potassium content were all tested. The experimental results show that the minerals accelerate the fixation of organic and inorganic carbon in the soil and also promote amaranth growth. Moreover, the available potassium content was increased when K-feldspar was added. Taken together, adding moderate amounts of carbonate and silicate minerals into the soil is found to be an attemptable way of accelerating CO2 fixation and improving the potassium content of soil.